2010
DOI: 10.2967/jnumed.110.079376
|View full text |Cite
|
Sign up to set email alerts
|

Pretargeted 177Lu Radioimmunotherapy of Carcinoembryonic Antigen–Expressing Human Colonic Tumors in Mice

Abstract: Pretargeted radioimmunotherapy (PRIT) with bispecific antibodies in combination with a radiolabeled peptide reduces the radiation dose to normal tissues, especially the bone marrow. In this study, the optimization, therapeutic efficacy, and toxicity of PRIT of colon cancer with a 177 Lu-labeled peptide was determined in mice with carcinoembryonic antigen (CEA)-expressing human tumors. Methods: To obtain the optimal therapeutic efficacy, several strategies were evaluated to increase the total amount of radioact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
41
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 46 publications
(42 citation statements)
references
References 24 publications
1
41
0
Order By: Relevance
“…The activity in the tumor lesions as measured with SPECT correlated well with uptake measured with ex vivo biodistribution. In a previous study, we showed that successive administrations of PRIT within a 3-d interval resulted in similar uptake in the tumors (5). Therefore, images acquired after diagnostic or therapeutic administrations of PRIT can be compared quantitatively.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The activity in the tumor lesions as measured with SPECT correlated well with uptake measured with ex vivo biodistribution. In a previous study, we showed that successive administrations of PRIT within a 3-d interval resulted in similar uptake in the tumors (5). Therefore, images acquired after diagnostic or therapeutic administrations of PRIT can be compared quantitatively.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, 10 mL of 50 mM ethylenediaminetetraacetic acid were added in order to complex any unbound 111 In or 177 Lu. Radiochemical purity of the radiolabeled IMP288 preparations was determined by reversed-phase high-performance liquid chromatography as described previously (5). In all experiments, the radiochemical purity of radiolabeled IMP288 exceeded 95%.…”
Section: Pretargeting Reagents Tf2 and Imp288mentioning
confidence: 99%
See 1 more Smart Citation
“…The use of TF2, composed of a humanized anti-HSG Fab fragment derived from the 679 anti-HSG mAb and 2 humanized anti-CEA Fab fragments derived from the hMN-14 mAb (labetuzumab; Immunomedics, Inc.) by the dock-and-lock procedure, should reduce immunogenicity and facilitate repeated injections (22). Moreover, the HSG peptide allows facile and stable labeling with different radiometals, such as 177 Lu or 90 Y, having favorable physical features that could improve pRAIT efficacy (23).…”
Section: Discussionmentioning
confidence: 99%
“…In the context of preclinical studies that yielded encouraging results, TF2 was pre-administered to mice and allowed to localize to CEA-expressing tumors, followed by the injection of 177 Lu-coupled IMP-288. 112 Similar approaches are now being evaluated in patients affected by CEA-expressing malignancies, including colorectal and small cell lung cancer ( Table 4).…”
Section: Monoclonal Antibodies Under Early (Phase I-ii) Clinical Evalmentioning
confidence: 99%